Gastric mucosal repair by Men’s Huwei Powder via EGF-NO/PGE2-PI3K-TLR4 in RELISH: Restoring Equilibrium through long-term integration of synergistic health - Xu, Kaijie; Li, Jing; Guo, Shoupeng; Zhang, Jin; Zhang, Xichun (Frontiers in Pharmacology, 2025)
Background:Gastric mucosal injury (GMI) involves inflammation, oxidative stress, and barrier dysfunction. Existing therapies offer limited efficacy with side effects. Men's Huwei Powder (MHWP), a Traditional Chinese Medicine (TCM) formula developed under the RELISH (Restoring Equilibrium through Long-term Integration of Synergistic Health) framework, aims to restore mucosal and systemic equilibrium.Methods:The experiment was grouped using a uniform design, followed by the construction of an ethanol-induced GMI rat model. The effects of MHWP were assessed through histological examination, ELISA, RT-PCR, 16S rRNA sequencing, and LC-MS-based serum fingerprint analysis. Multivariate modeling techniques, including SPRA, PLSR, and pSEM, were utilized to explore the comprehensive regulatory mechanisms of MHWP.Results:MHWP promotes activation of the EGF–NO/PGE2 axis and concurrently suppresses key nodes of the PI3K/Akt/NF-κB signaling pathway, leading to downregulation of pro-inflammatory cytokines—including IL-1β, IL-6, and TNF-α—in both serum and gastric tissue. Beyond its localized effects, MHWP exerts systemic benefits by inhibiting hepatic TLR4, MyD88, and NF-κB expression, thereby reducing liver-derived IL-6 and TNF-α and ameliorating ethanol-induced liver injury. This hepatic protection contributes to improved gastric mucosal healing and systemic inflammatory balance. Gut microbiota profiling identified key genera—such as Ligilactobacillus, Acutalibacter, and Lachnospiraceae:CAG_95—as critical mediators of mucosal repair, with MHWP modulating their abundance in a botanicals–dependent manner. These genera were closely linked to the regulation of NO, COX-2, and gastric IL-1β and IL-6, highlighting their critical role in the EGF–NO/PGE2 axis and inflammatory signaling. Serum HPLC fingerprinting identified several bioactive metabolites—including 6-gingerol (P1), atractylenolide II (P10), and dihydrostilbene base + 3O,2Prenyl (P18)—as major contributors to MHWP's efficacy. Closely associated with specific botanical drugs, these metabolites synergistically regulated multiple inflammatory and reparative pathways, underscoring MHWP's holistic therapeutic mechanism.Conclusion:MHWP exerts multi-targeted effects through integrated modulation of the liver, gut microbiota, and serum metabolites. These findings underscore its potential as a holistic and sustainable TCM-based intervention for GMI, in alignment with the RELISH framework.